2014
DOI: 10.18093/0869-0189-2014-0-2-84-90
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Antioxidant Enzymes on the Tracheal Epithelium Regeneration After Chemical Burn

Abstract: Различные ожоги органов дыхания сопровождаются массовой гибелью клеток эпителиальных тканей (слизистые трахеи, бронхов), что приводит к исклю-чительно тяжелым последствиям для здоровья чело-века. Поэтому чрезвычайно важным является созда-ние новых лекарственных препаратов для лечения такого вида травм.Острые патологические процессы в организме сопровождаются мощным окислительным стрессом (гиперпродукция активных форм кислорода -АФК), который является одним из основных пора-жающих факторов, при этом лавинообраз… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…It should be mentioned that we have demonstrated earlier a powerful cytoprotective effect of exogenous Prdx6, using models of chemical and thermal burns of the upper respiratory tract in rats, which was manifested in a significant preservation (by 50% higher compared to the control) of the ciliated epithelium of the trachea [ 50 ]. This can be explained not only by the elimination of a wide range of hydroperoxides in the damaged area, but also, obviously, by the ability of Prdx6 to be effectively reduced and re-engaged (due to aiPLA2) in the antioxidant defense of epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…It should be mentioned that we have demonstrated earlier a powerful cytoprotective effect of exogenous Prdx6, using models of chemical and thermal burns of the upper respiratory tract in rats, which was manifested in a significant preservation (by 50% higher compared to the control) of the ciliated epithelium of the trachea [ 50 ]. This can be explained not only by the elimination of a wide range of hydroperoxides in the damaged area, but also, obviously, by the ability of Prdx6 to be effectively reduced and re-engaged (due to aiPLA2) in the antioxidant defense of epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments in animal models of diseases accompanied by development of oxidative stress showed that application of exogenous Prdx6 can correct the pathologic process course and facilitate faster recovery of damaged organs and tissues [103,106,107,108]. Particularly, exogenous Prdx6 application alleviates the severity of ionizing radiation damage, increasing the survival rate of animals exposed to sublethal and lethal doses [110,111].…”
Section: Discussionmentioning
confidence: 99%
“…Infusion of Prdx6 before the action of the aforementioned factors provides suppression of oxidative stress, thus preventing the damage of actively proliferating tissues. Prdx6 infusion after the damage, for example, after thermal burns of the upper respiratory tract, leads to a faster recovery of tissues, suppression of cell necrosis, and apoptosis [108,109]. Thus, the obtained experimental data has evidenced that exogenous Prdx6 possesses a high antioxidant potential and could be promising in the treatment of pathologies accompanied by the development of oxidative stress, particularly, those caused by ionizing radiation.…”
Section: Application Of Exogenous Prdx6 As a Radioprotectormentioning
confidence: 99%